DTUF-PS: A Design Thinking-Based Usability Framework for Android Harvest Monitoring in Oil Palm Plantations - Novita Novita; Hilyah Magdalena (Politeknik Ganesha Medan, 2026)
One of Indonesia’s major plantation commodities is oil palm, but the still-manual documentation process hinders operational efficiency and real-time monitoring. Although the use of Design Thinking in mobile app development is growing, critical gaps remain, such as the lack of research that systematically integrates plantation-specific parameters—for example, the Harvest Density Index, Average Bunch Weight, and rotation cycle—into a usability evaluation framework tailored to the cognitive load of field workers. This study aims to develop and evaluate a prototype of an Android-based harvest monitoring system using a UI/UX approach and the Design Thinking method. The study involved 30 respondents, consisting of 5 division assistants and 25 field workers, and utilized the System Usability Scale (SUS), User Experience Questionnaire (UEQ), and time efficiency measurements. Empirical findings show an average SUS score of 80 (SD=6.1), categorized as “Good” (70th percentile), UEQ Perspicuity of 1.79 (85th percentile), “Very Good,” and a 69.9% increase in time efficiency from 600.6 to 180.7 seconds, paired t-test p<0.001, Cohen’s d=4.03, with instrument reliability confirmed by Cronbach’s α ranging from 0.73 to 0.87). The main contribution of this study is the Design Thinking-Based Usability Framework for Plantation Systems (DTUF-PS), which introduces three transferable constructs: Domain Artifact-Driven Empathize (DADE), Parameter-Embedded Ideation (PEI), and the Triadic Usability Evaluation Model (TUEM). This framework is proposed as an initial transferable model that requires further validation in other plantation contexts, such as rubber, cocoa, and coffee. The research results indicate that the Design Thinking method is effective in meeting user needs in agricultural monitoring.